The relationship between rheumatoid factor levels and coronary artery lesion complexity and severity in patients with stable coronary artery disease - Alizade, Elnur (Postepy Kardiol Interwencyjnej, 2015)
INTRODUCTION: The relation between serum rheumatoid factor levels and the extent, severity, and complexity of coronary artery disease has not been adequately studied. AIM: Therefore, we assessed the relationship between the severity of coronary artery disease assessed by SYNTAX score and serum rheumatoid factor levels in patients with stable coronary artery disease. MATERIAL AND METHODS: We enrolled 268 consecutive patients who underwent coronary angiography. Patients with acute coronary syndrome and chronic immune disorders were excluded. Baseline serum rheumatoid factor levels were measured and the SYNTAX score was calculated from the study population. RESULTS: Patients were divided into two groups. Group 1 was defined as low SYNTAX score < 22, and group 2 was defined as intermediate and high SYNTAX score > 22. Serum rheumatoid factor levels were significantly higher in the intermediate and high-SYNTAX score group than in the low-SYNTAX score group (16.4 ±9 IU/mlvs. 11.36 ±5 IU/ml, p < 0.001). Also, there was a significant correlation between rheumatoid factor and CRP levels with the SYNTAX score r = 0.411; p < 0.001 and r = 0.275; p < 0.001, respectively. On multivariate linear regression analysis, rheumatoid factor (β = 0.101, p < 0.001) was an independent risk factor for intermediate and high SYNTAX score in patients with stable coronary artery disease. In receiver operator characteristic curve analysis, optimal cut-off value of rheumatoid factor to predict high SYNTAX score was found to be 10.5 IU/ml, with 69% sensitivity and 61% specificity. CONCLUSIONS: The rheumatoid factor level was independently associated with the extent, complexity, and severity of coronary artery disease assessed by SYNTAX score in patients with stable coronary artery diseases.